Additive Design Mimics the Strength and Architect of Nature (Journal of Material Science and Technology Research, 2023)
Abstract: It is believed that the best parts’ design and performance is that which mimics the creation of nature. Palm is a very good example of an extra ordinary tree which must attract the attention of engineers and designers. In contrast with other types of trees, palms have a vascular, jumble, and spongy tissue stem instead of a wooden one. This is the reason why palm trees can with stand strong hurricanes while trees cannot. The stem of a palm is composed of three main parts. Those are the main stem body, the central core, and the leaves growing from the central core in circular and axial patterns along the core. This natural combination tissues of different construction provides an extra-flexibility to the main stem, enhance the relative movement of these components, and as a result enables the palm to bend massively without any catastrophic fracture. This exceptional construction inspired the author to design and manufacture a part which mimics the most public tree at the home country. The model was additively manufactured from 316L, tested for bending with and without heat treatment, and compare with cast part of similar material and dimensions. The aim was always to achieve improved mechanical properties and performance of AM parts with complex geometry.